Museum Genomics Provide Evidence for Persistent Genetic Differentiation in a Threatened Seabird Species in the Western Atlantic. (4th July 2022) - Byerly, Paige A; Chesser, R Terry; Fleischer, Robert C; McInerney, Nancy; Przelomska, Natalia A S; Leberg, Paul L
Abstract: Connectivity among wildlife populations facilitates exchange of genetic material between groups. Changes to historical connectivity patterns resulting from anthropogenic activities can therefore have negative consequences for genetic diversity, particularly for small or isolated populations. DNA obtained from museum specimens can enable direct comparison of temporal changes in connectivity among populations, which can aid in conservation planning and contribute to the understanding of population declines. However, museum DNA can be degraded and only available in low quantities, rendering it challenging for use in population genomic analyses. Applications of genomic methodologies such as targeted sequencing address this issue by enabling capture of shared variable sites, increasing quantity and quality of recovered genomic information. We used targeted sequencing of ultra-conserved Elements (UCEs) to evaluate potential changes in connectivity and genetic diversity of roseate terns ( Sterna dougallii ) with a breeding distribution in the northwestern Atlantic and the Caribbean. Both populations experienced range contractions and population declines due to anthropogenic activity in the 20th century, which has the potential to alter historical connectivity regimes. Instead, we found that the two populations were differentiated historically as well as contemporaneously, with little evidence of migration between them for either time period. We also found no evidence for temporal changes in genetic diversity, although these interpretations may have been limited due to sequencing artifacts caused by the degraded nature of the museum samples. Population structuring in migratory seabirds is typically reflective of low rates of divergence and high connectivity among geographically segregated subpopulations. Our contrasting results suggest the potential presence of ecological mechanisms driving population differentiation, and highlight the value of targeted sequencing on DNA derived from museum specimens to uncover long-term patterns of genetic differentiation in wildlife populations.